Third Party’s Intellectual Property Rights And The Seller’s Liability Under The United Nations Convention On International Sale Of Goods (CISG) And The Sale Of Goods Act (SGA) - Kiraz, Serife E. (University of Leicester, 2019)
This thesis is a comparative analysis of the provisions on the seller’s duty to deliver the goods free from any third-party intellectual property rights (IPRs) under the United Nations Conventions on the International Sale of Goods (CISG) and the UK Sale of Goods Act 1979 (SGA). As a consequence of technological advancement, there has been an increased observance of the interaction between intellectual property rights (IPRs), which are intangible property rights, and tangible goods. As a result of this interaction, growing numbers of goods, which are either subject to IPRs as a whole or that possess an IP-protected component, have become subject to sales agreements. The circulation of the goods around the world increases the likelihood that third-party IPRs over the goods will be infringed. This risk of infringement also raises the possibility that the application of IP law remedies will prevent the buyer from reselling or using the goods in question. This study is concerned with the question of how the sale of goods is affected by third-party IPRs, and it proposes to undertake a comparative analysis of the provisions that determine the seller’s liability when third-party IPRs arise in relation to goods that are sold under the CISG and the SGA. It seeks to determine which instrument offers sufficient protection that will benefit the buyer. In attempting to reveal the sufficient protection, it also undertakes a comparative analysis of the remedies that are available to the buyer under the CISG and the SGA when third-party IPRs over the goods are raised. With regard to the widely acceptance of the CISG by 89 states, and the dominant role of English law in commercial law and its preference as a governing law to most contracts, it is aimed to determine the differences and similarities between the CISG and the SGA, and the practical consequences of their application to the contracts when third-party IPRs over the goods arise. The thesis will seek to determine if the text of the relevant CISG articles can be improved and will accordingly formulate proposals that work towards this outcome.

Article 6.8 and Annex II of the WTO agreement on antidumping - Persoz, Dimitri (European University Institute, 2019)
Article 6.8 of the Antidumping Agreement (AD) allows domestic investigating authorities to make determinations on the basis of the best information available (BIA) when any interested party does not cooperate during an antidumping investigation under the discipline of Annex II of the AD. Since its introduction, this provision has been the source of extensive and neverending litigation in front of both domestic investigating authorities and the Dispute Settlement Body. In this thesis, we research to what extent the findings of the Panels and the Appellate Body regarding Article 6.8 AD are consistent with the mandate set out in Articles 3.2, 11 DSU and 17.6 AD and to what extent they are reasonable from an economic perspective. To answer the first question, we first discuss Articles 3.2, 11 DSU and 17.6 AD to establish what is the mandate of the Panels and the Appellate Body under the Dispute Settlement Body. We then examine the findings of the Panels and the Appellate Body in the interpretation of the seven terms of Article 6.8 AD under the previously established mandate. To answer the second question, we summarize the latest developments in the economic theory of adjudication and litigation. We then discuss the findings of the Panels and the Appellate Body using this economic standard. In the conclusion, we compare the results of our analysis with current negotiations on Article 6.8 AD in the Doha Round framework and further discuss the opportunity to create a single united international investigating authority.

Unification of international sales law in the SADC region : the role and significance of the CISG - Simelane, Mbalenhle Pearl (University of Johannesburg, 2019)
The United Nations Commission on International Trade Law (UNCITRAL) is one of the most prominent legal bodies in international commerce. In 1980, the final draft of the United Nations Convention on Contracts for the International Sale of Goods (CISG or the Convention) was approved by the United Nations (UN) General Assembly and came into operation on 1 January 1988. Generally, the diversity of laws is an impediment to international and regional trade. Traders are discouraged from entering into international sales contracts due to the dissimilarities of legal systems. However, the CISG seeks to unify laws relating to the international sale of goods, whilst codifying the existing rules of international trade. The main objectives of the Southern African Development Community (SADC) are to achieve development and economic growth through regional integration.1 The legal integration and unification of sales law has a significant role to play in regional integration. Hence, SADC would do away with difficulties that affect interregional and intra-regional trade by impeding economic growth by making use of widely accepted trade laws, such as the Convention. International trade promotes both economic development and social upliftment. Moreover, democracy, political stability and human rights must be respected to foster sustainable economic growth and development in Southern Africa. 2 With advantages such as accessibility, flexibility, indorsing party autonomy, simplicity, and uniform interpretation, the paper revisits the call for the unification of laws on the sale of goods in SADC and considers the role and significance of the CISG in the region. LL.M. (Commercial Law)
Keywords: Commercial law; International economic integration; International trade Law; International unification